The Emotional Balance and Its Relationship with Social Support among the Elderly in Care Homes in the Governorates of Bethlehem and Jericho - Abu Haltam, Ala Said; Al-Halabiyah, Fadwa Abdallah (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify emotional balance and its relationship to social support among the elderly in nursing homes in the governorates of Bethlehem and Jericho. To achieve the study objective, the researcher adopted the descriptive correlational approach and the questionnaire tool. The study sample included (88) elderly people who were selected using the available sample method (Convenience). The study results showed that there is no relationship between the level of emotional balance and social support. As for the results of emotional balance among the elderly, it came at an average degree of (3.27), and it became clear that there were no differences attributed to the variables: gender, economic level, educational level, age, social status, and health status, with differences attributed to the variable of having children and the source of support. As for the results of social support, it was average with a total degree of (3.05). It became clear from the results of the differences in the averages of the level of social support among the elderly, that there are no differences attributed to the variables: gender, economic level, having children, age, and length of residence in the home. The elderly, social status, and health status, while it became clear that there were differences attributed to the variable of educational level, health status, and differences attributed to the variable of source of support, and the differences were in favor of the source of support, the family. The study recommends sufficient encouragement to build social relationships and social support to increase emotional balance among the elderly and help them face daily problems and make decisions.